KOMODIFIKASI KESENIAN WAYANG KULIT DALAM FILM PEREMPUAN TANAH JAHANAM PERSPEKTIF MARXIAN - RIZKY SULAIMAN SALIM; AKBAR RAMADHAN MUHAMMAD; AG EKA WENATS WURYANTA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
Film is one of the effective media in mass communication and also a commodity that drives the wheels of the creative economy. Through films there are values that are used as spectacles, which can be converted into rupiah. This is the discourse of commodification begins. The purpose of this study is to find the possibility of the commodification of wayang kulit art which is one of the Javanese cultural heritages in the film Wanita Tanah Jahanam. These cultural values are consciously used to support the mystical concepts in the story and are sold as a lucrative commodity for the film industry. The analysis is guided by the theory of commodification of Marxism which states that commodification is the process of producing any goods or services to be traded. This research uses descriptive qualitative field study (naturalistic inquiry) method to explain phenomena captured and understood by the author. The research approach used is media ethnography, in which researchers ’’ inhabit ’’ the film Woman Land of Hell intensely, and at certain intervals to get certain protests. The results of the study are that there are three commodifications of puppet art in this film. First, the puppeteer is projected as someone who not only plays in the area of art, but goes beyond that by highlighting his metaphysical abilities. It is precisely this metaphysical ability that is congruent with the theme of the film that sells this two-dimensional mysticism. The second is the ending of the puppet show which is not in the form of aesthetic satisfaction and things that give life lessons, but rather the sadism of the puppeteer who killed Sinden and others. That’s what was sold to the audience. Third is the mystification of art. In this context, it is shown by making puppets made from human skin / human skin. This mystification is so that wayang children are perceived to have certain magical powers. Apparently this is also positioned as an important commodity in the film industry in the country.